Tinjauan Perhitungan Rencana Anggaran Biaya (RAB) Non-Struktur dan Penjadwalan Pada Pembangunan Kantor Kejaksaan Negeri Tual - Fathin Azzahra Suat; La Mohamat Saleh; Maslan Abdin (Jurnal Multidisiplin Teknologi dan Arsitektur, 2026)
Development is a continuous process carried out to improve the sosial and economic indicators of a region over time. One of the important stages in the emplementation of a construction project is the calculation of the Budget Plan (RAB), as it serves to answer question related to the total cost required for a building. In the construction project of the District Attomey’s Office, particularly as a public facility, budget planning is curcial to ensure the project runs according to plan. This study aims to determine the non-structural work budget using the Unit Price Analysis (AHSP) PUPR No.8 of 2023 and the 2024 Basic Price data, as well as to analyze the project duration using the Critical Path Method (CPM) and S-Curve method. The results of the study show that the estimated cost of non-structural work is IDR 1,538,390,000.00. For scheduling, the duration obtained was 5 months using the S-Curve method and 89 weeks using the CPM method. Thus, these findings provide a comprehensive overview of the cost and time requirements for the implementation of the Tual District Attorney’s Office construction project.